Perspectives on an Acceptance and Commitment Therapy (ACT) based program for patients with inflammatory bowel disease and comorbid anxiety and/or depressive symptoms. (4th July 2021) - Dober, Madeleine; Mikocka-Walus, Antonina; Evans, Subhadra; Beswick, Lauren; Emerson, Catherine; Olive, Lisa
Abstract: Background and aim : Individuals with inflammatory bowel disease (IBD) suffer higher rates of anxiety and depression than the general population, however, few psychological interventions are designed for this population. Acceptance and Commitment Therapy (ACT), aimed to increase psychological flexibility, may be useful to address the unique concerns of IBD sufferers. This study aimed to explore stakeholder perspectives on an ACT-based intervention prototype tailored to people with IBD and comorbid anxiety and/or depressive symptoms. Methods : An Intervention Mapping methodology guided intervention design. A qualitative exploratory design was used to investigate the perspectives of stakeholders. Focus groups or interviews obtained feedback from IBD patients of a major regional hospital, and health providers to IBD patients Australia-wide. Results : Findings were analysed using template analysis. Data saturation was reached at 19 participants (11 patients and 8 health professionals). Participants' perspectives on the ACT-based intervention were distributed across four themes: (1) Barriers to access and participation; (2) Timing in the illness trajectory; (3) ACT is useful for IBD; and (4) The more support, the better. Conclusion : The findings suggest that an ACT modality and blended delivery design is well received by patients and health professionals, providing recommendations to future researchers and clinicians on intervention design.